"We have to wake up and smell the flowers". Interview with Stephen Marglin - Stephen Marglin (Intervention. European Journal of Economics and Economic Policies, 2011)
First paragraph: Stephen, our first question is plain and simple: How did you become an economist?
Keywords: 330